2016
DOI: 10.1595/205651316x691960
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Induced Deactivation and the Corresponding Strategies for Improving Durability in Automotive Three-Way Catalysts

Abstract: Increasingly demanding exhaust emissions regulations require that automotive three-way catalysts (TWC) must exhibit excellent catalytic activity and durability. Thus, developing TWC based on an accurate understanding of deactivation mechanisms is critical. This work briefly reviews thermally induced deactivation mechanisms, which are the major contributor to deactivation, and provides an overview of the common strategies for improving durability and preventing deactivation. It highlights the interaction of met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 0 publications
0
30
0
Order By: Relevance
“…During this start-up period, the low engine exhaust temperature (typically \ 250°C) only slowly raises the temperature of the catalyst itself. 9 However, good conversions are typically only achieved at temperatures . 300°C.…”
Section: Hc + No X + Hv ! O 3 + Other ð1þmentioning
confidence: 99%
“…During this start-up period, the low engine exhaust temperature (typically \ 250°C) only slowly raises the temperature of the catalyst itself. 9 However, good conversions are typically only achieved at temperatures . 300°C.…”
Section: Hc + No X + Hv ! O 3 + Other ð1þmentioning
confidence: 99%
“…Many functional oxides, including the important example of ceria-zirconia mixed oxides, typically have surface areas of only 2 m 2 /g under operating conditions [84]. It is obviously desirable to maximize surface area in order to improve catalytic performance, while providing a better stability of the functional oxide.…”
Section: High-surface-area Functional Oxidesmentioning
confidence: 99%
“…Platinum-based catalysts have been widely used in the chemical industry for the catalytic dehydrogenation of light alkanes, such as ethane and propane [1,2], as well as the automotive industry to catalytically oxidize harmful pollutants, including CO, NO, and hydrocarbons [3][4][5][6]. Ceria has been used in automotive catalysts, due to its oxygen storage capacity and the ability to stabilize active metals [7][8][9]. The recognized ability of ceria to undergo rapid reduction/oxidation cycles (4CeO 2 2Ce 2 O 3 + O 2 ) plays a significant role in providing oxygen mobility and oxygen storage/release [8].…”
Section: Introductionmentioning
confidence: 99%
“…Ceria has been used in automotive catalysts, due to its oxygen storage capacity and the ability to stabilize active metals [7][8][9]. The recognized ability of ceria to undergo rapid reduction/oxidation cycles (4CeO 2 2Ce 2 O 3 + O 2 ) plays a significant role in providing oxygen mobility and oxygen storage/release [8]. In our previous investigations, it was reported that the synergy between ceria additive and active Pt species has a positive impact on the stability of coordinately unsaturated Pt 2+ and Pt 4+ species, thereby drives C-C and C-H bonds activation and promotes low-temperature oxidation of propane [10].…”
Section: Introductionmentioning
confidence: 99%